Claws for alarm - Brown, Rita Mae; Brown, Sneaky Pie, 1982- (Mrs. Murphy mystery, 2021)
"A thrilling new tale from New York Times bestselling author Rita Mae Brown and her feline co-author Sneaky Pie Brown. Death stalks the Blue Ridge Mountains once again and Mary Minor "Harry" Harristeen, along with her beloved cats, is on the case"--